GAA-FGF14 ataxia (SCA27B): phenotypic profile, natural history progression and 4-aminopyridine treatment response - Wilke, Carlo; Pellerin, David; Mengel, David; Traschütz, Andreas; Danzi, Matt C; Dicaire, Marie-Josée; Neumann, Manuela; Lerche, Holger; Bender, Benjamin; Houlden, Henry; Züchner, Stephan; Schöls, Ludger; et al. (Brain (London, England : 1878), 2023)
Ataxia due to an autosomal dominant intronic GAA repeat expansion in FGF14 [GAA-FGF14 ataxia, spinocerebellar ataxia 27B (SCA27B)] has recently been identified as one of the most common genetic late-onset ataxias. We here aimed to characterize its phenotypic profile, natural history progression, and 4-aminopyridine (4-AP) treatment response. We conducted a multi-modal cohort study of 50 GAA-FGF14 patients, comprising in-depth phenotyping, cross-sectional and longitudinal progression data (up to 7 years), MRI findings, serum neurofilament light (sNfL) levels, neuropathology, and 4-AP treatment response data, including a series of n-of-1 treatment studies. GAA-FGF14 ataxia consistently presented as late-onset [60.0 years (53.5-68.5), median (interquartile range)] pancerebellar syndrome, partly combined with afferent sensory deficits (55%) and dysautonomia (28%). Dysautonomia increased with duration while cognitive impairment remained infrequent, even in advanced stages. Cross-sectional and longitudinal assessments consistently indicated mild progression of ataxia [0.29 Scale for the Assessment and Rating of Ataxia (SARA) points/year], not exceeding a moderate disease severity even in advanced stages (maximum SARA score: 18 points). Functional impairment increased relatively slowly (unilateral mobility aids after 8 years in 50% of patients). Corresponding to slow progression and low extra-cerebellar involvement, sNfL was not increased relative to controls. Concurrent second diseases (including progressive supranuclear palsy neuropathology) represented major individual aggravators of disease severity, constituting important caveats for planning future GAA-FGF14 trials. A treatment response to 4-AP with relevance for everyday living was reported by 86% of treated patients. A series of three prospective n-of-1 treatment experiences with on/off design showed marked reduction in daily symptomatic time and symptom severity on 4-AP. Our study characterizes the phenotypic profile, natural history progression, and 4-AP treatment response of GAA-FGF14 ataxia. It paves the way towards large-scale natural history studies and 4-AP treatment trials in this newly discovered, possibly most frequent, and treatable late-onset ataxia.